Waywaya 11 Filipino stories - Jose, Francisco Sionil 1924- author (Solidaridad Publishing House, 1985)
These eleven short stories, culled from F. Sionil José's prodigious production in the last decade, are a moving commentary on the Filipinos. "Waywaya" recreates pre-Hispanic Philippine society and should also be read as allegory. In Sionil José's own language, Ilokano, "Waywaya" means freedom. The last story in the collection, "Progress", has been anthologized abroad and regarded as contemporary social document as well.